Choosing to die with the help or by the hand of a doctor (medically-assisted death): Limitations and safety profiles - F. Cembrani; D. De Leo (International Journal of Science Annals)
Background and Aim of Study: Depression severity can be profoundly impacting the life of individuals, while its persistence can provoke the conviction that recovery is unattainable. One of the extreme consequences is the request for euthanasia. However, during major depression cognition can be significantly impaired. In this study, we comment on the exemplar case of a Belgian lady, Mrs. Godelieva de Troyer, who made that request and obtained the desired outcome. The aim of the study: to consider a specific case of a patient with major depressive disorder and the role of doctors in informing the decision about medically assisted death. Material and Methods: The history of the request made by Mrs. Godelieva is described. The procedure was followed by the reactive initiatives of the son of the lady, who made a formal complaint against the procedure that brought his mother to death and appealed the European Court of Justice. Results: A description of what happened is briefly reported, including considerations on the clinical treatments received by Mrs. Godelieva, the roles interpreted by the doctors she consulted and, finally, the appropriateness of the decision taken. Conclusions: In revisiting this case, the decision-making process during major depression episodes and the authenticity and robustness of end-of-life choices in similar cases are critically examined. Comments are made on the frequency of cognitive impairments during major depressive episodes and the need to provide depressed people the necessary support during their important choices.